2022
DOI: 10.3390/su14095231
|View full text |Cite
|
Sign up to set email alerts
|

Does Servant Leadership Promote Emotional Intelligence and Organizational Citizenship Behavior among Employees? A Structural Analysis

Abstract: The last two decades have seen a conspicuous rise in the importance of leadership styles. Servant Leadership (SL) is believed to be a pioneering style of leadership that aims to serve others first. Based on the Social Learning Theory and Social Exchange Theory, this study investigates whether SL promotes Organizational Citizenship Behavior (OCB) among employees. In this regard, it also examines what role the employees’ Emotional Intelligence (EI) plays between the two variables. A sample of 422 responses was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 94 publications
2
17
0
1
Order By: Relevance
“…Dynamic firms give utmost importance to CSR activities since they act as leading factors in formulating corporate strategies [21,22]. The rules and norms of business responsibility and the organization's general obligations are reflected in explicit and implicit CSR policies [23].…”
Section: Corporate Social Responsibility In the Restaurant Industrymentioning
confidence: 99%
“…Dynamic firms give utmost importance to CSR activities since they act as leading factors in formulating corporate strategies [21,22]. The rules and norms of business responsibility and the organization's general obligations are reflected in explicit and implicit CSR policies [23].…”
Section: Corporate Social Responsibility In the Restaurant Industrymentioning
confidence: 99%
“…On the other hand, EI has been at the center of controversy throughout the years despite a growing body of academic research. A very recent study focusing on Pakistan explored EI among managers and concluded that “leaders who can serve their follower’s needs and expectations to the best of their abilities could promote and strengthen EI among their employees, which eventually boosts their followers’ behavior’s emotional and motivational aspects” (Kumari et al , 2022). The literature review revealed different models that propose various conceptualizations of the EI construct (Larsen et al , 2003; Kanesan and Fauzan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, previous research supports an association among servant leadership and numerous positive employee outcomes, such as improving employee motivation (Kumari et al, 2022), ethical behaviours (Sendjaya et al, 2019), and organizational commitment (Lapointe & Vandenberghe, 2018). Further, employees of servant leaders have been found to be more likely to engage in tasks outside of the scope of their immediate job description to assist their coworkers and their organization (Chiniara & Bentein, 2016).…”
Section: Servant Leadershipmentioning
confidence: 80%
“…In line with this, servant leaders also empower followers in ways such as incorporating their input into important decisions, including them in various organizational processes, and providing them with opportunities to enhance their skills (Hunter et al, 2013). It has also been suggested that servant leadership promotes a positive work climate and subsequently results in positive employee outcomes, such as increases in employee well-being (Parris & Peachey, 2013), productivity (Kumari et al, 2022), and job satisfaction (Guillaume et al, 2013). Additionally, servant leadership has been found to decrease both employee turnover intentions (Kashyap & Rangnekar, 2016) and employee deviance (Paesen et al, 2019).…”
Section: Servant Leadershipmentioning
confidence: 99%
See 1 more Smart Citation